The Principal's Strategy in Preparing Teacher Professionalism at SD IT Roudhotul Ilmi Ansho - Rolin Fadilah Hasibuan; Candra Wijaya; Fatkhur Rohman (South Sulawesi Education Development (SSED), 2024)
The principal, as a leader, must possess several abilities, including personal skills, knowledge of educational staff, the school's vision and mission, decision-making abilities, and communication skills. This research is a qualitative study with a descriptive approach. The data collection methods used in this study include observation, interviews, and documentation. For data analysis, the study employs the analysis framework by Huberman and Miles, which consists of data reduction, data display, and conclusion drawing. The validity of the data is ensured through Lincoln and Guba's criteria, including credibility, transferability, dependability, and confirmability. The findings of this study show that: 1). The strategy of the principal at SD IT Roudhotul Ilmi Anshor in preparing teacher professionalism involves examining and assessing teachers' competency levels, providing guidance and motivation, offering opportunities, conducting evaluations, and giving rewards to teachers. 2). The principal's performance in preparing teacher professionalism is evaluated based on several competencies, including personality competence, managerial competence, entrepreneurial competence, supervisory competence, and social competence. 3). An effective strategy for the principal in preparing teacher professionalism involves closely observing teachers' abilities, providing guidance and motivation, offering opportunities and training, conducting evaluations, and giving rewards to teachers.